The Effect of Profitability, Asset Structure and Company Liquidity on Capital Structure with Investment Opportunity Set as Intervening Variable - Theresia Somasiga Faulu Daeli; Srimulyantini Srimulyantini; Dianwicahsih Arieftiara; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2022)
The purpose of the study is to show the Effect of Profitability, Asset Structure and Company Liquidity on Capital Structure with the Investment Opportunity Set as the Intervening Variable. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2019. The data for this study were taken from the company's annual report. The number of samples in this study are 22 companies which selected by purposive sampling. The results of the hypothesis in this study using panel data regression method and the EViews application. The results in this study are Profitability, Asset structure and Liquidity have a significant effect on Capital Structure and Profitability. Keywords:Profitability, Asset Structure, Liquidity, Capital Structure, Investment Opportunity Set